Wound Closure with Transcutaneous Absorbable Polyglactin Sutures after Hidradenitis Suppurativa Excision. (February 2022) - Drogt, Carolyn; Hanwright, Philip; Ha, Michael; Ngaage, Ledibabari M.; Lin, Mary; Ge, Shealinna; Wu, Yinglun; Silverman, Ronald P.; Rasko, Yvonne M.
ABSTRACT: OBJECTIVE: Wide surgical excision is the standard treatment for severe hidradenitis suppurativa (HS). Because of the nature of HS, these wounds are often nonsterile, located in moist intertriginous regions, and closed under tension, increasing the risk for surgical site complications. Although uncommon, absorbable sutures may confer benefits over nonabsorbable material for skin closure. Accordingly, the authors evaluated the use of absorbable, braided, transcutaneous polyglactin sutures after wide surgical excision of HS. METHODS: The authors performed a retrospective chart review for all consecutive patients who underwent wide surgical excision of HS at a tertiary university hospital between January 2009 and March 2020. RESULTS: Sixty consecutive patients with 174 operative sites were included in the study. The surgical site complication rate was 17.8%. Postoperative complications included wound dehiscence (n = 18), surgical site infection (n = 2), and scar contracture (n = 1). Sutures were removed from 12 (6.9%) operative sites. Factors influencing complications were Hurley grade and area of excision. Complications did not differ significantly among disease locations ( P = .6417). CONCLUSIONS: The results support the growing evidence that absorbable sutures are an appropriate option after wide surgical excision of HS.